Fairness in times of crisis: Negative shocks, relative income and preferences for redistribution - Anna Hochleitner (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
While economic crises tend to raise questions about a fair distribution of resources, less is known about whether and how fairness views themselves are affected by negative shocks. To answer this question, I conduct two experimental studies investigating the causal link between income shocks and preferences for redistribution. While Study 1 exogenously manipulates within experiment shocks, Study 2 capitalises on the recent Covid-19 crisis and investigates the behaviour of subjects hit by real world income shocks. The results from Study 1 show that allocation decisions as well as reactions to shocks depend on participants' relative income. Participants who are relatively poorer exhibit little reaction to shocks and distribute resources in line with an egalitarian fairness view. Participants who are relatively richer, by contrast, distribute resources proportionate to individual contributions and are quite responsive to shocks. They allocate more to themselves if they suffered a shock, but less if the other faced a shock. Study 2 confirms that negative shocks affect redistributive preferences with participants allocating more to individuals who suffered the Covid-19 shock. The results contribute to a growing literature on context-dependent preferences and show that economic shocks can have a substantial impact on the demand and acceptance of redistributive policies.
Keywords: D31; D63; D91; C91; 330; Redistribution; Inequality; Fairness; Laboratory-Individual Behavior